Au-delà des frontières, sept sociologies du travail - Le Comité de Rédaction de la NRT (La Nouvelle Revue du Travail, 2021)
This NRT Corpus offers a presentation of the sociology of work (SoW) in seven countries other than France. The list includes older European cradles of social sciences such as Germany or the United Kingdom (the Spanish sociology have started much later) along with the United States. Countries often referred to as possessing an “emerging” school - such as Mexico, Argentina and China – are also treated here. Each article has its own way of analysing and critiquing how research objects have been transformed ; how issues and paradigms have emerged or disappeared ; and how paradigms have dominated or faded. Each also reflects convergences between intellectual currents —a circulation of ideas within which the effects of capitalism’s transformations can be read — while also noting the differences between all these branches of sociology.